Developing a Feasible and Credible Method for Analyzing Healthcare Documents as Written Data - Tanja Moilanen; Mari Sivonen; Kirsi Hipp; Hanna Kallio; Oili Papinaho; Minna Stolt; Riitta Turjamaa; Arja Häggman-Laitila; Mari Kangasniemi (SAGE Publishing, 2022)
Healthcare provides a rich, and constantly increasing, number of written documents, which are underutilized in research data for health and nursing sciences, but previous literature has only provided limited guidance on the process of document analysis. The aim of this paper is to provide a methodological framework for analyzing health care documents as written data, based on a systematic methodological review and the research team's experience of the method. Based on the results, the methods consist of seven phases: (i) identify the purpose, (ii) determine the document selection strategy, (iii) select or design an extraction matrix, (iv) carry out pilot testing, (v) collect and analyze the data, (vi) consider the credibility, and (vii) ethics of the study. The framework that has been developed can be used to carry out document analysis studies that are both feasible and credible.